Religious Liberty, Immigration Sanctuary, and Unintended Consequences for Reproductive and LGBTQ Rights - Keeley, Laura (Columbia Journal of Gender and Law, 2019)
This Note considers the idea that potential religious liberty claims could be made by faith-based communities to provide sanctuary for undocumented immigrants and pays particular attention to potential unintended consequences those claims could have in the areas of reproductive and LGBTQ rights. Arguments to justify religious liberty in the name of sanctuary could be used in the future by different parties in attempts to limit reproductive rights and discriminate against LGBTQ persons. The announcement by President Trump of the creation of a new oversight entity in the Department of Health and Human Services, the Conscience and Religious Freedom Division, is an example of this religious-liberty-as-discrimination phenomenon. This Note proposes that any religious liberty claims made in the name of sanctuary should 1) be evaluated in the domain of antidiscrimination law and not analogized to much broader “conscience clauses”; 2) advocate for a narrower construction of religious liberty jurisprudence and religious liberty-protecting statutes, such as the Religious Freedom Restoration Act (RFRA); and 3) push courts to evaluate the sincerity of sincerely held religious beliefs.